I-FABP as biomarker for the early diagnosis of acute mesenteric ischemia and resultant lung injury. - Rachel G Khadaroo; Spyridon Fortis; Saad Y Salim; Catherine Streutker; Thomas A Churchill; Haibo Zhang (PLoS ONE)
Acute mesenteric ischemia (AMI) is a life-threatening condition that can result in multiple organ injury and death. A timely diagnosis and treatment would have a significant impact on the morbidity and mortality in high-risk patient population. The purpose of this study was to investigate if intestinal fatty acid binding protein (I-FABP) and α-defensins can be used as biomarkers for early AMI and resultant lung injury. C57BL/6 mice were subjected to intestinal ischemia by occlusion of the superior mesenteric artery. A time course of intestinal ischemia from 0.5 to 3 h was performed and followed by reperfusion for 2 h. Additional mice were treated with N-acetyl-cysteine (NAC) at 300 mg/kg given intraperitoneally prior to reperfusion. AMI resulted in severe intestinal injury characterized by neutrophil infiltrate, myeloperoxidase (MPO) levels, cytokine/chemokine levels, and tissue histopathology. Pathologic signs of ischemia were evident at 1 h, and by 3 h of ischemia, the full thickness of the intestine mucosa had areas of coagulative necrosis. It was noted that the levels of α-defensins in intestinal tissue peaked at 1 h and I-FABP in plasma peaked at 3 h after AMI. Intestinal ischemia also resulted in lung injury in a time-dependent manner. Pretreatment with NAC decreased the levels of intestinal α-defensins and plasma I-FABP, as well as lung MPO and cytokines. In summary, the concentrations of intestinal α-defensins and plasma I-FABP predicted intestinal ischemia prior to pathological evidence of ischemia and I-FABP directly correlated with resultant lung injury. The antioxidant NAC reduced intestinal and lung injury induced by AMI, suggesting a role for oxidants in the mechanism for distant organ injury. I-FABP and α-defensins are promising biomarkers, and may guide the treatment with antioxidant in early intestinal and distal organ injury.